2002
DOI: 10.1002/psc.385
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of heterotrimeric collagen peptides containing the α1β1 integrin recognition site of collagen type IV

Abstract: Collagen type IV provides a biomechanically stable scaffold into which the other constituents of basement membranes are incorporated, but it also plays an important role in cell adhesion. This occurs with collagen type IV mainly via the alpha1beta1 integrin, and the proposed epitope involved in this type of collagen/integrin interaction corresponds to a non-sequential R/Xaa/D motif, where the arginine and aspartate residues are provided by the alpha2 and alpha1 chains of the collagen molecule, respectively. Si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
35
0

Year Published

2003
2003
2007
2007

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 32 publications
(37 citation statements)
references
References 53 publications
2
35
0
Order By: Relevance
“…Conversely, for the correct registration and assembly of heterotrimeric collagen peptides containing functional sequence portions of natural collagens, we have introduced a simple artificial C-terminal cystine knot exploiting regioselective cysteine pairing procedures to align the three peptide chains via two interchain-disulfide bridges into the desired staggers. 29,31,[53][54][55] Modeling and molecular dynamics (MD) simulations served to optimally fit the cystine knot into the triple-helix without steric clashes, 29 a fact that was recently confirmed by NMR structural analysis of a model peptide containing such disulfide connectivities. 56 In view of the positive experiences with these disulfide-cross-linked collagenous heterotrimers and also because of the presence of a cystine knot downstream from the ␣1␤1 adhesion epitope, the two heterotrimers A and B ( Figure 2) were selected as possible mimics of the ␣1␤1 adhesion epitope of collagen type IV.…”
Section: Design Of Cell-adhesive Collagen Type IV Mimeticamentioning
confidence: 95%
See 2 more Smart Citations
“…Conversely, for the correct registration and assembly of heterotrimeric collagen peptides containing functional sequence portions of natural collagens, we have introduced a simple artificial C-terminal cystine knot exploiting regioselective cysteine pairing procedures to align the three peptide chains via two interchain-disulfide bridges into the desired staggers. 29,31,[53][54][55] Modeling and molecular dynamics (MD) simulations served to optimally fit the cystine knot into the triple-helix without steric clashes, 29 a fact that was recently confirmed by NMR structural analysis of a model peptide containing such disulfide connectivities. 56 In view of the positive experiences with these disulfide-cross-linked collagenous heterotrimers and also because of the presence of a cystine knot downstream from the ␣1␤1 adhesion epitope, the two heterotrimers A and B ( Figure 2) were selected as possible mimics of the ␣1␤1 adhesion epitope of collagen type IV.…”
Section: Design Of Cell-adhesive Collagen Type IV Mimeticamentioning
confidence: 95%
“…56 In view of the positive experiences with these disulfide-cross-linked collagenous heterotrimers and also because of the presence of a cystine knot downstream from the ␣1␤1 adhesion epitope, the two heterotrimers A and B ( Figure 2) were selected as possible mimics of the ␣1␤1 adhesion epitope of collagen type IV. 55 These trimers contain the sequence portions 457-468 of the aligned ␣1 and ␣2 chains of collagen type IV which encompass the residues 461 directly involved in binding to ␣1␤1 integrin. While in the trimer B the synthetic peptide chains are aligned in the ␣2␣1␣1Ј register with ␣2 as the leading chain according to the stagger proposed for collagen type IV, 15 in the trimer A the less probable ␣1␣2␣1Ј register was applied to analyze the effect of the chain register on integrin binding affinities.…”
Section: Design Of Cell-adhesive Collagen Type IV Mimeticamentioning
confidence: 99%
See 1 more Smart Citation
“…However, not all integrins recognize the RGD sequence, and some integrins recognize sites consisting of amino acids from more than one protein subunit, such as sequences in the triple helical domain of collagen (Sacca and Moroder, 2002). In addition to overlooking ligands, several of the abovementioned assays may identify ligands that are not relevant at physiological concentrations of integrin and ligand.…”
Section: Introductionmentioning
confidence: 99%
“…Another approach, peptide display by filamentous phage, has been used successfully to identify peptide ligands, such as integrin-ligand mimetics (Koivunen et al, 1994(Koivunen et al, , 1995, but has not identified physiologically relevant ligands. However, this may not be an ideal approach since the binding site of ligands is often derived from multiple segments of the protein that may not be contiguous (Sacca and Moroder, 2002).…”
Section: Introductionmentioning
confidence: 99%